Dasar Pertimbangan Hakim Terhadap Tindak Pidana Pencurian Yang Dilakukan Oleh Anak - Nurul Aqsha Irawan; Elly Sudarti; Nys. Arfa (CV. ITTC INDONESIA, 2025)
This study aims to determine and analyze Decision Number: 12/Pid.Sus-Anak/2021/PN.Nab whether it has reflected the values of legal certainty, legal justice, legal benefits. In this study, the problems reviewed are regarding 1) What is the basis for the judge's considerations in imposing sanctions on children who commit the crime of theft in Decision Number: 12/Pid.Sus-Anak/2021/PN. Nab? 2) Is the decision handed down by the judge against the defendant in Decision Number: 12/Pid.Sus-Anak/2021/PN Nab in accordance with the principles of juvenile justice? The research method used in this paper is Normative Juridical Research. This research approach uses a Statutory Approach by conducting research on legal products, a Conceptual Approach based on theories, legal concepts, and legal principles relevant to the problem and a Case Study Research Approach based on court decisions that have permanent legal force that analyzes the Nabire District Court decision Number: 12/Pid.Sus-Anak/2021/PN Nab, studying and interpreting applicable legal regulations. The Judge's considerations in decision Number: 12/Pid.Sus-Anak/2021/PN.Nab are legally in accordance with legal provisions, but do not fully reflect the principle of ultimum remedium in the juvenile criminal justice system. Imprisonment for children is not always the best solution, especially if the goal is development. Judges in sentencing children should be based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. As explained, sentencing emphasizes the concept of restorative justice which prioritizes resolving juvenile criminal cases outside the judicial system.